PENGARUH KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM MAKMUR MANDIRI BANTEN - Perando Sitanggang; Suprapto Suprapto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine whether there is a positive and significant influence between Leadership and Job Stress partially or simultaneously on Employee Performance at KSP Makmur Mandiri Banten. This study uses an associative quantitative research method where the data obtained is in the form of a questionnaire that is processed using the SPSS 2.2 application. the result is that the tcount value of the Leadership variable is 2.834 which is greater than the ttable value of 1.99655 with a significant level of 0.004 less than 0.05, which means that Ha is accepted and Ho is rejected, so it can be concluded that leadership has a positive and significant effect on employee performance. The tcount value of the Job Stress variable is 2,187 greater than the ttable of 1.99655 with a significant level of 0.032 less than 0.05, which means that Ha is accepted and Ho is rejected. So that it can be concluded partially that work stress has a positive and significant effect on employee performance. it is known that the Fcount is 21,503 and the significance value is 0.009 while the Ftable value is 3.14. So it can be concluded that Fcount > Ftable (21,503> 3.14) and significance <0.05 (0.009 <0.05), then Ha is accepted, so it can be concluded that Leadership and Work Stress together affect employee performance at KSP Makmur Mandiri Banten